BERITA BOHONG DAN MENYESATKAN TENTANG INFORMASI PRODUK DALAM KONTRAK ELEKTRONIK - Sudjana, Sudjana (Fakultas Hukum Universitas Komputer Indonesia, 2022)
Freedom of expression through the use of Information Technology is carried out by taking into account the restriction not to contain false and misleading news. This study aims to determine the legal consequences of false and misleading news regarding product information in electronic contracts and to formulate the legal liability of business actors against false and misleading news about product information in electronic contracts. Typology The research methods are normative research, legal approach, data collection techniques through document studies and qualitative data analysis methods. The results of the study show that false news related to product information in electronic contracts violates subjective conditions, resulting in the agreement being cancelled, while